The Integration of Occupational Pension Policies: Lessons for Canada - Kpessa, M.W.; Hering, M. (University of Toronto Press, 2008)
Is the integration of occupational pension policies across the Canadian provinces feasible? In this paper, we assess the proposal for harmonization made by the Canadian Association of Pension Supervisory Authorities (CAPSA) by comparing it to the EU’s successful integration of member states’ pension regulations. We argue that CAPSA’s initiative failed both because regulatory diversity was defined as a fundamental problem and because the regulations that serve social policy goals were not protected from integration. We suggest that occupational pension integration in Canada would be feasible if provincial governments largely excluded rules on benefits and relied primarily on the mutual recognition of regulations
Keywords: Occupational pensions; regulation; agenda-setting; problem definition; Canada; European Union